PERKEMBANGAN PERMUKIMAN DI BANTARAN SUNGAI SURABAYA DARI PERSPEKTIF SOSIOLOGI - Soenyono Soenyono (LPPM UNY, 2006)
This research aims to describe the development of settlement in the bank of Surabaya River from colonial era to 2006. This is a historic qualitative research. Data are collected through observation, interview and documentation. The setting of the research includes Kampung Baru, Jagir, Gunungsari, and Kebraon. Data are analyzed using interaction model of Miles and Huberman (1994). Based on the result of the research, it can be concluded that (1) the settlements in the bank of Surabaya River have been established since 1358 M, (2) From 19th century, the development of Surabaya follows the stream of Kali Mas, to the south, due to the river was the vital transportation, (3) there was dispute to get stren area in 1961. The significant increase number of settlement in that area was in 1976-1980, and the peak was in 2001, (4) the process to get stren area are various, different from one area to another. Some of the people directly stay. Others ways are to claim, manage, buy, get permission, and get from parents